IMPROVEMENT OF 1VPU FIBER CLEANER (Journal of Science-Innovative Research in Uzbekistan, 2024)
In order to eliminate the shortcomings of the 1VPU type fiber cleaner used in cotton cleaning enterprises, we offer improved fiber cleaning equipment. The difference between this construction and the existing one is the installation of additional columns in the working chamber. As a result, the cleaning surface becomes larger and the cleaning efficiency is expected to increase by 0.5-1.0%